Catalpol Modulates Lifespan via DAF-16/FOXO and SKN-1/Nrf2 Activation in Caenorhabditis elegans. (2nd March 2015) - Seo, Hyun Won; Cheon, Se Myung; Lee, Myon-Hee; Kim, Hong Jun; Jeon, Hoon; Cha, Dong Seok
Abstract : Catalpol is an effective component of rehmannia root and known to possess various pharmacological properties. The present study was aimed at investigating the potential effects of catalpol on the lifespan and stress tolerance using C. elegans model system. Herein, catalpol showed potent lifespan extension of wild-type nematode under normal culture condition. In addition, survival rate of catalpol-fed nematodes was significantly elevated compared to untreated control under heat and oxidative stress but not under hyperosmolality conditions. We also found that elevated antioxidant enzyme activities and expressions of stress resistance proteins were attributed to catalpol-mediated increased stress tolerance of nematode. We further investigated whether catalpol's longevity effect is related to aging-related factors including reproduction, food intake, and growth. Interestingly, catalpol exposure could attenuate pharyngeal pumping rate, indicating that catalpol may induce dietary restriction of nematode. Moreover, locomotory ability of aged nematode was significantly improved by catalpol treatment, while lipofuscin levels were attenuated, suggesting that catalpol may affect age-associated changes of nematode. Our mechanistic studies revealed that mek-1, daf-2, age-1, daf-16, and skn-1 are involved in catalpol-mediated longevity. These results indicate that catalpol extends lifespan and increases stress tolerance of C. elegans via DAF-16/FOXO and SKN-1/Nrf activation dependent on insulin/IGF signaling and JNK signaling.